Plant design and operations - Sutton, Ian (Engineering professional collection, 2015)
This book provides practical guidance on the design, operation, and maintenance of process facilities to managers, engineers, operators, and maintenance specialists. It is supported by useful, real-world examples and experience from a wide range of facilities and industries and includes guidance on occupational health and safety, industrial hygiene and personal protective equipment. Topics covered include: energy control; safety in design; security, equipment, and transportation. A logical, practical guide to maintenance task organization is provided, from conducting a job hazards analysis to the issue of a work permit, and to the shutdown and isolation of equipment. Common hazards are covered in detail, including flow problems, high pressure, corrosion, power failure, and many more. --